The Effect Of Perceived Ease Of Use And Perceived Trust On Behavioral Intention Quick Response Code Indonesian Standard (QRIS) In Mediating Risk Perceptions Among Student In Lubuklinggau - Sri Endang Susilawati; Herman Paleni; Indrawati Mara Kesuma (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study examines the influence of perceived ease of use and trust on QRIS adoption decisions, with perceived risk as a mediating variable among university students in Lubuk Linggau City. Employing a quantitative explanatory design, primary data were collected via questionnaires from respondents experienced in digital payments. The population comprised 10,079 students from local higher education institutions, and a sample of 100 was selected using Slovin’s formula with a 10% margin of error and purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (SEM-PLS) to assess direct and indirect relationships among variables. Findings reveal that both perceived ease of use and trust positively and significantly influence QRIS adoption. Ease of use encourages adoption through accessibility and operational simplicity, while trust strengthens decisions via security, data integrity, and service provider credibility. Additionally, perceived risk significantly mediates the relationship between ease of use and adoption, indicating that reducing perceived risk enhances technology adoption. These results suggest that usability, trust, and risk management are key factors in promoting QRIS adoption among students. Practically, the study highlights the need to improve system usability, reinforce security, and implement effective communication strategies to enhance trust and minimize perceived risk. This research contributes to a more comprehensive understanding of digital payment adoption in higher education.